2002
DOI: 10.1002/jrs.954
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic study of phase transitions in Li3PO4

Abstract: Although three forms of lithium phosphate are known, a complete structural description of the highest temperature polymorph has not yet been given. In the present work, the phase transitions of lithium phosphate were investigated at high temperatures using Raman microscopy and x-ray powder diffraction. Both transitions were observed by following the temperature dependence of the totally symmetrical Raman stretching vibration of PO 4 3− . Currently available structural information on the a form, resulting in P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
31
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 14 publications
6
31
0
1
Order By: Relevance
“…A model structure obtained by tripling one of the parameters in the unit cell of the lowtemperature form (ˇ) 85 gives P-O bond lengths far outside the normal expected range for orthophosphates. Valence bond calculation showed that the structure was not reliable; 10 bond valence sums at the P atoms were in good agreement with expected formal oxidation state of P 5C for the first two forms (ˇand ), but not for the third form (˛). In order to gain an insight into its structure, phase transitions of Li 3 PO 4 were monitored by Raman spectroscopy.…”
Section: Applicationmentioning
confidence: 87%
See 1 more Smart Citation
“…A model structure obtained by tripling one of the parameters in the unit cell of the lowtemperature form (ˇ) 85 gives P-O bond lengths far outside the normal expected range for orthophosphates. Valence bond calculation showed that the structure was not reliable; 10 bond valence sums at the P atoms were in good agreement with expected formal oxidation state of P 5C for the first two forms (ˇand ), but not for the third form (˛). In order to gain an insight into its structure, phase transitions of Li 3 PO 4 were monitored by Raman spectroscopy.…”
Section: Applicationmentioning
confidence: 87%
“…In order to gain an insight into its structure, phase transitions of Li 3 PO 4 were monitored by Raman spectroscopy. 10 The previously established correlation [Eqn (11), Fig. 1 Table 5).…”
Section: Applicationmentioning
confidence: 99%
“…Fortunately, there have been several reports of experimental measurements of Raman and infrared absorption spectra of crystalline Li 3 PO 4 (Tarte (1967); Harbach and Fischer (1974); Riedener et al (2000); Smith et al (2002); Mavrin et al (2003); Popović et al (2003)); therefore our simulations of the zone center phonon modes serve as a validity check the calculations. Figure 1 shows two similar but distinct crystal structures of Li 3 PO 4 for which the normal modes have been studied.…”
Section: Calculational Methodsmentioning
confidence: 96%
“…IV was taken from Ref. [Popović et al (2003)]. These are compared with calculated results using PAW and USPP formalisms and LDA and GGA exchange-correlation functionals.…”
Section: Calculational Methodsmentioning
confidence: 99%
“…15,16 The β form is also stable but it irreversibly transforms to the γ phase at high temperatures (400-600 • C). [17][18][19] The γ-Li 3 PO 4 has an orthorhombic Pnma structure (#62), which is similar to the well-studied olivine cathode materials: LiFePO 4 , FePO 4 , etc. 20 There has been some theoretical research on β and γ-Li 3 PO 4 solid electrolytes.…”
mentioning
confidence: 95%